Efikasi Kartu Senyum Berpengaruh terhadap Peningkatkan Derajat Kebersihan Gigi dan Mulut pada Anak Sekolah Dasar - Jusuf Kristianto; Dwi Priharti; Minarni Minarni (Poltekkes Kemenkes Jakarta III, 2018)
School dental health services are implemented in an integrated manner through primary dental and oral health activities at the Puskesmas with the main UKS activities in the form of Usaha Kesehatan Gigi Sekolah (UKGS) program.Various methods are used to achieve maximum dental and oral health, such as promotion and demonstration of toothbrushes for elementary school children. One way to improve your child's behavior in the oral hygiene is to provide dental health education on how to brush your teeth is good and right with using tools or proper and appropriate media. A Smile Card is one of the right methods to change children's behavior in maintaining dental and oral hygiene.This study aims to determine the effect of the Smile Card on the health of the teeth and mouth of children, in children who do not have parentsThe sample is 150 people divided into intervention and control groups. The results showed that there were differences in the influence of knowledge and without the role of parents on improving dental and oral hygiene between the groups given the Smile Card intervention with the group not given the Smile Card, where p = 0.001 <0.05.It can be concluded that knowledge and companion roles influence the improvement of children's oral and dental hygiene.